A STUDY ON PREPARATION AND HYDRIDING OF -Mg2Al3 AND -Mg17Al12 - Hadi Suwarno (PTBN - BATAN, 2009)
ABSTRACT A Study on Preparation and Hydriding OF b-Mg2Al3 AND g-Mg17Al12. The mechanism of the synthetic formation of b-Mg2Al3 and g-Mg17Al12 has been studied. Mechanical alloying of Mg and Al powders with the atomic ratio of Mg:Al = 2:3 in toluene solution yields b-Mg2Al3 compound after milling for 30 h. The g-Mg17Al12 can be formed by heating the b-Mg2Al3 at 430 °C under high vacuum. The measured hydrogen capacities of b-Mg2Al3 and g-Mg17Al12 as hydrided at 300 °C are 3.2 and 4.9 wt%, respectively. Microstructure of the Mg-Al specimen shows that on hydriding at 300 °C the polygonal shape of the g-Mg17Al12 changes into irregular shapes which are composed of g-MgH2 and Al. FREE TERMS: mechanical Alloying, Mg-Al compounds, hydriding ABSTRAK STUDI PENYIAPAN DAN HIDRIDING b-Mg2Al3 DAN g-Mg17Al12. Mekanisme pembuatan b-Mg2Al3 dan g-Mg17Al12 telah dipelajari. Pemaduan mekanik serbuk Mg dan Al dengan perbandingan atomik Mg:Al = 2:3 dalam larutan toluena menghasilkan senyawa b-Mg2Al3 setelah penggerusan selama 30 jam. g-Mg17Al12 dapat terbentuk dengan pemanasan b-Mg2Al3 pada suhu 430 °C dalam vakum tinggi. Kapasitas hidrogen terukur dari b-Mg2Al3 dan g-Mg17Al12 terhidrisasi pada suhu 300 °C adalah berturut-turut 3,2 dan 4,9% berat. Mikrostruktur dari spesimen Mg-Al menunjukkan bahwa sewaktu hidriding pada suhu 300 °C bentuk poligonal dari g-Mg17Al12 berubah menjadi tak beraturan yang terdiri dari g-MgH2 dan Al. KATA KUNCI: pemaduan mekanik, senyawa Mg-Al, hidriding